THE IMPACT OF FINANCIAL TECHNOLOGY ADOPTION ON FINANCIAL MANAGEMENT EFFICIENCY IN SMALL AND MEDIUM ENTERPRISES - Muhammad Azizi; Irdawati Irdawati; Andi Primafira Bumandava Eka; Mutmainah Mutmainah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to analyze the impact of Financial Technology (FinTech) adoption on financial management efficiency in Small and Medium Enterprises (SMEs). The rapid development of digital technology has transformed various aspects of business financial management, including payment systems, accounting processes, cash flow management, and access to financing. This research employs a literature review approach by examining relevant scholarly articles, books, reports from international organizations, and academic publications related to FinTech adoption and SME financial management. The collected data were analyzed using thematic analysis to identify major themes, patterns, and relationships between FinTech utilization and financial management efficiency. The findings indicate that FinTech adoption positively influences SME financial management efficiency by improving transaction speed, enhancing financial reporting accuracy, facilitating access to financing, and supporting better managerial decision-making. Furthermore, digital financial technologies contribute to reducing operational costs and increasing financial transparency. Despite these benefits, several challenges remain, including limited digital literacy, cybersecurity risks, and organizational technological readiness. The study concludes that FinTech serves as a strategic tool capable of enhancing financial management efficiency while promoting business sustainability and competitiveness in the digital economy. Therefore, broader FinTech adoption is essential for strengthening SME performance and supporting long-term economic development.